Integrating Foot Reflexology and Barefoot Walking in Type 2 Diabetes Mellitus Care: A Case Study - Jayapal, Praveena; Selvam, Mohanamathiyal; Sankar, Geethanjali (Indian Journal of Integrative Medicine, 2025)
Diabetes mellitus, a major global health challenge is characterised by persistent hyperglycaemia due to insulin dysfunction. Effective management often necessitates exploring adjunctive therapies alongside conventional treatments. This case study examines Acupuncture and Energy Medicine (AEM) for managing Type 2 Diabetes Mellitus (T2DM). A 60-year-old male, recently diagnosed with T2DM, presented with an HbA1c of 11% with the symptoms of giddiness and excessive sweating. These interventions aimed to evaluate foot reflexology, barefoot walking, and diet therapy on glycemic control and overall health. The patient participated in a twelve-month program incorporating these modalities. Reflexology sessions, targeting zones associated with the pancreas, liver, and kidneys, were conducted twice daily. Pre- and post-intervention assessments included Fasting Blood Glucose (FBS), Post Prandial Blood Glucose (PPBS), HbA1c, Height, Weight, Blood Pressure and Body Mass Index (BMI). Results revealed a substantial improvement in the glycaemic control. HbA1c decreased to 8%, FBS and PPBS levels showed marked reductions, and BMI was slightly reduced. The patient reported increased energy levels, reduced dizziness, and improved overall well-being. This case highlights the potential benefits of integrating holistic therapies such as foot reflexology and barefoot walking into diabetic care. These interventions may improve the metabolic parameters and address psychosocial aspects, facilitating a patient-centred approach to diabetes management. Larger prospective studies are warranted to substantiate these findings and establish standardized protocols.